ISSUES OF ORGANIZATION OF MANAGEMENT ACCOUNTING AT THE ENTERPRISE (World Economics and Finance Bulletin, 2023)
The paper deals with the application of modern methods of cost management in the organization of management accounting at the enterprise.
Keywords: Costs; management accounting; management analysis